Women migrant workers and counter-trafficking responses in Association of Southeast Asian Nations: The enduring challenge of safety and security - Segrave, Marie Therese (Journal of criminology, 2021)
Drawing on a study undertaken across eight Association of Southeast Asian Nations countries in 2019, this article focuses on the persistence of investment in criminal justice infrastructure and mechanisms 20 years after the Palermo Protocol came into effect. We examine the enduring challenges and limitations around counter trafficking responses that remain removed from the lived realities of women migrant workers. Building on qualitative interviews with stakeholders and women migrant workers, we argue that women's protection from migration and labor exploitation and gendered violence remains elusive. This study highlights how counter-trafficking systems undermine women's safety and argues for a move away from siloed trafficking efforts, toward a much broader commitment to upholding women migrant workers? rights and protection.